Antimicrobial Stewardship Programs in Northwest China: A Cross-Sectional Survey of Perceptions, Involvement, and Perceived Barriers Among Hospital Pharmacists - Ji, Wenjing; Hayat, Khezar; Ye, Dan; McIver, David J.; Yan, Kangkang; Kadirhaz, Muhtar; Shi, Li; Liu, Xiaofeng; Chen, Hanjie; Fang, Yu (Frontiers in Pharmacology, 2021)
Background: Antimicrobial stewardship (AMS) is a key prevention strategy in addressing the global concern of increasing antimicrobial resistance (AMR). Pharmacists are one of the integral members of AMS hospital teams around the world. Toward reducing AMR, a major strategy in China is to improve the capacity and participation of pharmacists in the AMS framework. However, little is known about how hospital pharmacists perceive their position and participation in AMS work, and the barriers to this work in China, especially in the northwest. Methods: This work describes a cross-sectional, anonymous, online survey study. Hospital pharmacists from five provinces/autonomous regions in northwest China were invited to participate in June and July 2020. Participants completed the survey by using WeChat, a popular social application in China. We purposefully distributed the questionnaire link and QR code to hospital pharmacists through the hospital antimicrobial resistance surveillance network, hospital antimicrobial consumption surveillance network, provincial and city pharmaceutical association, and hospital pharmacist WeChat groups. Results: Out of 1032 respondents, 93.1% believed that AMS programs promote the judicial prescribing of antimicrobials, 95.5% strongly agreed that AMS could reduce the widespread use of antimicrobials, and 92.3% believed that AMS could improve medical services. Pharmacists were most likely to be involved in AMS through reviewing prescriptions of antimicrobials, intervening in inappropriate prescriptions, and providing feedback on antimicrobial prescriptions and medical orders. Barriers to participating in AMS included workload (59.5%), ineffective communication between pharmacists and doctors (57.7%), and inadequate knowledge of AMS (47.0%). Differences in responses were found between the five provinces. A significant association was found between median involvement scores with gender, age, education, level of superiority, experience, and type of hospital (p<0.05). Conclusions: Pharmacists perceived that AMS programs are important, but their participation in AMS related activities was found to be poor in all provinces. Further studies and strategies should consider how to overcome the identified barriers to optimize the participation of pharmacists in AMS programs.